Latin and Languages for special purposes: pro et contra (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with a problem of professionally oriented teaching Latin in non-linguistic universities. The author in a polemical manner considers attempt to transfer the concept of "Language for special purposes" on the ground of teaching Latin for medics, pays great attention to the nuances of terminology.
Keywords: professional linguodidactics; language for special purposes; Latin